Allen Tate - Glass, John V., III (Book collections on Project MUSE., 2016)
"This book reassesses the importance of Allen Tate (1899-1976), a former U.S. Poet Laureate, as a uniquely Southern and fundamentally religious poet and a critic. Through close analysis of Tate's essays and poems, the author argues that the arc of Tate's career presents a coherent effort to understand the Modernist's sense of the "dissociated sensibility, and that in his conversion to Catholicism, he found the means of rediscovering unified existence"--